Technologie und Kommunikation: Innovationsschübe vor dem Hintergrund der Außenbeziehungen Altägyptens - Wilde, Heike (Mobilität und Wissenstransfer in diachroner und interdisziplinärer Perspektive, 2013)
What effect do spatial mobility and migrations have on the diffusion of knowledge? In this volume, papers dealing with the topic have been collected from various culture-historical and theoretical disciplines. Chronologically they range from non-literate cultures to an insight into contemporary research on economic innovation. The interdisciplinary contributions reveal in different ways the relationships between spatial mobility and the transfer of knowledge, thus allowing the phenomenon to be structured in both historical and non-literate ages.